Numerical solution of a Volterra integral equation - Ahmed Abdulkareem Hadi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This work deals with a generalized nonlinear Volterra integral equation of the second kind, in whose kernel the unknown function occurs with two different arguments. The equation is solved by a collocation approach with piecewise Hermite polynomials. When using polynomials of degree 2 m- 1, m e N, and suitable quadrature formulas, the method has the order 2 m. The collocation points must be chosen in accordance with a stability condition.